Determinants Of Pregnant Women's Compliance In Carrying Out Antenatal Care Visits - Lestari Tampubolon, Ida; Harahap, Novy Ramini (Universitas Prima Indonesia, 2025)
Antenatal care during pregnancy aims to detect early high-risk pregnancy and childbirth so that it can reduce maternal mortality. Currently in Indonesia every day there are maternal deaths related to pregnancy, childbirth, and the postpartum period, the World Health Organization (WHO) reports that maternal deaths are estimated at 500,000 deaths each year and 99% of them occur in developing countries. Objective: To determine factors related to compliance with antenatal care visits in pregnant women. Method; analytical survey with a cross-sectional approach. The population is all pregnant women in Trimester III who come to the Pratama Ridho Clinic as many as 30 people. The sampling technique was Accidental Sampling and 25 respondents were obtained. The data used were primary data and tested using the chi-square test. Results; From the chi-square test between family support and compliance with ANC visits, the p-value = 0.000 was obtained, the distance factor of residence was obtained p-value = 0.002, the perception factor p-value 0.031 and parity p-value 0.039. Conclusion; There is a relationship between family support visits, distance from residence to clinic, perception and parity of pregnant women with compliance with ANC visits at the Ridho Medan Pratama Clinic in 2024. It is hoped that families will provide support to pregnant women so that they are compliant in making ANC visits.